Higher-Order Models in the Theory of Planned Behavior to Predict Whistleblowing Intention - Hamdani, Ujang; Roekhudin; Hariadi, Bambang (Jurnal Bina Praja, 2022)
The low rank of Indonesia's Corruption Perception Index (CPI) 2021 indicates that government fraud is still a significant problem. One improvement in bureaucracy reform is the whistleblowing system to report wrongdoing. Although this system is applicable, the effectiveness of whistleblowing as a mechanism to detect fraud depends on the willingness of an employee to report misconduct. As a part of government management systems in local government, the internal auditor has a unique position to detect fraud as early as possible in their organization. They conduct regular monitoring of other agencies to know the fraud before. This research investigates internal auditors' intention to report fraud in the local government. By employing the theory of planned behavior, variables in this study were attitude toward whistleblowing, subjective norms, perceived whistleblowing control, and internal whistleblowing intention. This study was mixed-method research with a sequential explanatory design approach. Data were obtained from questionnaires of 201 internal auditors in local government and in-depth interviews to produce a complete study result. The researcher adopted a higher-order model in PLS-SEM to explain the relationship between components of the theoretical construct. Higher-order models facilitate a construct on a more abstract higher-level dimension and its more concrete lower-order subdimensions. The findings of this research revealed that attitude toward whistleblowing, subjective norms, and perceived whistleblowing control positively affected the intentions of the internal auditor to report wrongdoings internally. The result of this study can be implemented by the local government to effectively improve some policies related to moral education and whistleblowing systems.